Comparing the well-being of Para and Olympic sport athletes: a systematic review - Macdougall, H.; O'Halloran, P.; Shields, N.; Sherry, E. (Adapted Physical Activity Quarterly, 2015)
This systematic review included 12 studies that compared the well-being of Para and Olympic sport athletes. Meta-analyses revealed that Para athletes, compared with Olympic sport athletes, had lower levels of self-acceptance, indicated by athletic identity, d = -0.47, 95% confidence interval (CI) [-0.77, -0.16], and body-image perceptions, d = -0.33, 95% CI [-0.59, -0.07], and differed from Olympic sport athletes in terms of their motivation, indicated by a greater mastery-oriented climate, d = 0.74, 95% CI [0.46, 1.03]. Given an inability to pool the remaining data for meta-analysis, individual standardized mean differences were calculated for other dimensions of psychological and subjective well-being. The results have implications for professionals and coaches aiming to facilitate the well-being needs of athletes under their care. Future research would benefit from incorporating established models of well-being based on theoretical rationale combined with rigorous study designs.